Accommodation as a Basic Component of Tourism - Tsiganok, Igor (My University, 2013)
The forms of accommodation are analyzed. The notion of hotel is defined and its classification is given.
Keywords: готель; туризм; розміщення; отель; туризм; размещение; hotel; tourism; accommodation; кафедра іноземних мов професійного спрямування